Impact of morphological and mechanical components on inconel 625 grinding using common cylindrical grinding wheels - Ramamoorthy, Manivannan; Madeshwaren, Vairavel; Thangavel, Suresh; Rajpradeesh, Thangaraj (Mechanical Engineering for Society and Industry, 2024)
This study used a grinding technique based on Gas Tungsten Arc Welding (GTAW) to create walls composed of Inconel 625 alloy. Mechanical and microstructural (MM) adjustments are structural and mechanical alterations that take place during the additive manufacturing process of Inconel 625 grinding. A thorough examination of the modifications made to the nickel superalloy Inconel 625's (I-625) microstructure was conducted during the grinding process. A circular weave and a stringer bead design were used to construct the wall. Tensile properties and microstructural analyses were assessed for each wall. Using scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS), the fracture zones of the tensile specimens were examined. The microstructure is mostly composed of equiaxed dendrites, although a unique combination of discontinuous and continuous cellular dendrites can be observed along the cross-section. In tensile testing, circular woven walls performed better than stringer bead walls. The EDS and AFM results show that Ni and Cr make up the majority of the fracture zone, with traces of Nb and Mo. Because there are no lave phases, the fracture mode is ductile. The elemental mapping, which shows the homogenous dispersion of Ni and Cr inside the fracture zone, provides additional evidence in favor of the ductile failure mode. The UTS of the time-consuming TS samples is somewhat higher and exhibits a steadily rising bias in comparison to the specimens with quick TS. The highest level of the UTS sample is 10 %.